Novel Viral Vectors for Gene Therapy 2023 (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Viral vectors are gene transfer tools assembled from the backbones of naturally occurring viruses. These replication-incompetent vehicles transfer assigned payloads into eukaryotic cells. Numerous viral vector systems that influence cells or tissues have been used to perform basic and preclinical research. Some virus-derived vectors found their way into clinical practice.